Long noncoding RNA Q associates with Sox2 and is involved in the maintenance of pluripotency in mouse embryonic stem cells. (1st May 2020) - Jing, Ruiqi; Guo, Xudong; Yang, Yiwei; Chen, Wen; Kang, Jiuhong; Zhu, Songcheng
Abstract: Large intergenic noncoding RNAs (lincRNAs) in ESCs may play an important role in the maintenance of pluripotency. The identification of stem cell‐specific lincRNAs and their interacting partners will deepen our understanding of the maintenance of stem cell pluripotency. We identified a lincRNA, LincQ, which is specifically expressed in ESCs and is regulated by core pluripotent transcription factors. It was rapidly downregulated during the differentiation process. Knockdown of LincQ in ESCs led to differentiation, downregulation of pluripotency‐related genes, and upregulation of differentiation‐related genes. We found that exon 1 of LincQ can specifically bind to Sox2. The Soxp region in Sox2, rather than the high mobility group domain, is responsible for LincQ binding. Importantly, the interaction between LincQ and Sox2 is required for the maintenance of pluripotency in ESCs and the transcription of pluripotency genes. Esrrb and Tfcp2l1 are key downstream targets of LincQ and Sox2, since overexpression of Esrrb and Tfcp2l1 can restore the loss of ESC pluripotency that is induced by LincQ depletion. In summary, we found that LincQ specifically interacts with Sox2 and contributes to the maintenance of pluripotency, highlighting the critical role of lincRNA in the pluripotency regulatory network. Abstract : Schematic diagram shows the involvement of LincQ in ESC maintenance. Pluripotency transcription factors (Oct4, Sox2, and Nanog) promote the expression of LincQ. LincQ associates with Sox2 and activates the expression of pluripotency genes, such as Esrrb and Tfcp2l1, which are crucial for ESC maintenance. Depletion of LincQ in ESC leads to the downregulation of pluripotency genes and differentiation.